2019
DOI: 10.1002/ecs2.2538
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down pressure on a coastal ecosystem by harbor seals

Abstract: Historic hunting has led to severe reductions of many marine mammal species across the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 68 publications
1
25
0
9
Order By: Relevance
“…3, Table 1) (Minagawa and Wada 1984;Newsome et al 2010). Moreover, the important proportion of pelagic sandeels in German grey seal diet and of benthic resources in German harbour seal diet (Behrends 1985;Gilles et al 2008;de la Vega et al 2016;ICES 2018;Aarts et al 2019) is confirmed by the δ 34 S vs. δ 15 N, δ 34 S vs. T-Hg and δ 34 S vs. Se plots ( Fig.…”
Section: Germanymentioning
confidence: 79%
See 1 more Smart Citation
“…3, Table 1) (Minagawa and Wada 1984;Newsome et al 2010). Moreover, the important proportion of pelagic sandeels in German grey seal diet and of benthic resources in German harbour seal diet (Behrends 1985;Gilles et al 2008;de la Vega et al 2016;ICES 2018;Aarts et al 2019) is confirmed by the δ 34 S vs. δ 15 N, δ 34 S vs. T-Hg and δ 34 S vs. Se plots ( Fig.…”
Section: Germanymentioning
confidence: 79%
“…This may be related to the important proportion of benthic resources such as flatfish (e.g. plaice and sole) (Behrends 1985;Gilles et al 2008;de la Vega et al 2016;ICES 2018;Aarts et al 2019) according to different stomach content and stable isotope studies on southeast bay of the North Sea. The lower δ 15 N values of German grey seals may also be related to the high proportion of sandeels in their diet mostly present in offshore areas less frequented by harbour seals (Hall et al 1998;Rindorf et al 2019).…”
Section: Germanymentioning
confidence: 99%
“…Marine mortality of salmonids is influenced by several factors (Sobocinski et al 2018), including body size (Berg and Jonsson 1990;Jonsson and Jonsson 2009), timing of seaward migration (Jonsson and Jonsson 2009;, feeding efficiency and growth (Kennedy et al 2008;Henderson et al 2018;Jensen et al 2018a), environmental conditions (Gosselin et al 2018) pathogens (Gargan et al 2012;Gjelland et al 2014;Skaala et al 2014;Halttunen et al 2018) as well as predation by birds (Dieperink et al 2002;Wiese et al 2008) and seals. Harbour seals (Phoca vitulina, Linnaeus 1758) are abundant in the Wadden Sea (Reijnders et al 2010) and are growing in numbers in the area (Jensen et al 2015a;Aarts et al 2019). Seal density often correlate negatively with salmonid productivity (Nelson et al 2018) and seals may threaten salmonid species (Wright et al 2007;Thomas et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016/2017 werden er in de Voordelta 437 gewone zeehonden en 1478 grijze zeehonden geteld (Arts et al 2018). Het is lang niet duidelijk geweest wat de gewone zeehonden in de Waddenzee eten maar daar is recent onderzoek naar gedaan aan de hand van vissen otolieten in zeehonden uitwerpselen (Aarts et al 2018). (2018) het dieet gebaseerd op otolieten.…”
Section: Zeehondenunclassified